2018
DOI: 10.24843/ejmunud.2019.v08.i01.p14
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Organisasi Kepuasan Kerja Dan Komitmen Organisasional Terhadap Organizational Citizenship Behavior Pada Karyawan

Abstract: The purpose of this study is to determine the influence of organizational culture, job satisfaction and organizational commitment to organizational citizenship behavior. This research was conducted at the company Focus Design Artglass Ubud. The number of samples taken as many as 67 employees, using saturated sample technique, especially simple random sampling. The data were collected through questionnaires. The analysis technique used is multiple linear regression. Based on the analysis results found that orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 1 publication
2
3
0
10
Order By: Relevance
“…Fourth, organizational culture has a significant effect on The findings in this study are in line with research conducted by Erkutlu (2010), Jain (2015), Hardaningtyas (2004), Nugraha & Adnyani (2018), Mahayasa et al (2018) and Mahardika & Wibawa (2019) that organizational culture has a significant effect on OCB. P.T.…”
Section: Discussionsupporting
confidence: 90%
“…Fourth, organizational culture has a significant effect on The findings in this study are in line with research conducted by Erkutlu (2010), Jain (2015), Hardaningtyas (2004), Nugraha & Adnyani (2018), Mahayasa et al (2018) and Mahardika & Wibawa (2019) that organizational culture has a significant effect on OCB. P.T.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, it was found that this was following the initial hypothesis that Organizational Commitment and Authentic Leadership effect on OCB. These findings enhance previous research from Al Zaabi et al, (2016); Mahardika and Wibawa (2018);and Christian (2018). But in this study, it was also found that most employees were women by 61.6%.…”
Section: Discussionsupporting
confidence: 88%
“…Employees not only need to complete their duties in accordance with the job description, but also must be able to do a number of tasks in the company and have extra role behaviors that exceed the job description so that they can have a positive influence on the progress of the company. Harper mentioned that behaviors that are able to increase employee productivity in the company are extra-role behaviors or other names Organizational Citizenship Behavior (Mahardika & Wibawa, 2018). Ukkas and Latif (as cited in Samantha & Almalik, 2019) defines Organizational Citizenship Behavior (OCB) as an employee who completes work outside of his job description without coercion from other parties and is carried out voluntarily.…”
Section: Introductionmentioning
confidence: 99%
“…The research instrument will be a questionnaire specifically designed to measure organizational culture, OCB, work ethic and employee performance (Ermawati, 2023). The questionnaire will consist of items related to each variable, designed based on a conceptual framework that has been developed from related literature (Sitio, 2021).…”
Section: Data Collection Instrumentmentioning
confidence: 99%